From Aluminum Dissolution in Supercapacitors to Electroplating: A New Way for Al Thin Film Deposition? - Pietro Zaccagnini; Lars Henning Heß; Luisa Baudino; Marco Laurenti; Mara Serrapede; Andrea Lamberti; Andrea Balducci (Advanced Materials Interfaces, 2023)
Abstract The present work addresses a new finding observed while performing aluminum dissolution experiments for supercapacitors (SCs) stability investigation. Supercapacitor (SC) electrodes based on carbon‐coated aluminum foils are electrochemically cycled in harsh conditions into bis‐trifluoromethylsulfonyl imide (TFSI)‐based electrolyte and using Acetonitrile (ACN) as solvent. Dissolution of aluminum is observed with subsequent plating on the carbonaceous surface of counter electrodes. Moreover, the same process can be reproduced also on standard SC activated carbon electrodes. This mechanism can open the way to an effective strategy to achieve Al film deposition by electroplating becoming competitive with the most common copper counterpart.